The effects of anabolic-androgenic steroids upon resting and peak exercise left ventricular heart wall motion kinetics in male strength and power athletes - Climstein, M; O'Shea, P.; Adams, K. J.; de Beliso, M. (Journal of Science and Medicine in Sport, 2004)
Previous investigations reported alterations in myocardial fibres and systolic function associated with anabolic-androgenic steroid consumption by athletes. Advances in bio-medical technology have allowed further investigation in assessing the possible effects of anabolic-androgenic steroids on gross left ventricular kinetics. Twenty-three male strength and power athletes with a past and current history of anabolic-androgenic steroid consumption (x 46 days, range 28 days to 70 days), were compared to 23 controls. Testing consisted of resting and immediate post-exercise transthoracic left ventricular wall cardiokymograms. Statistical results identified no difference over time between groups or condition. Cardiokymographic waveform analysis found 32.61% of all (n =184) waveforms to be abnormal (Type II, n = 56 or Type III, n = 4). There were 14 treatment subjects (60.87%) who demonstrated an abnormal waveform as compared to 9 controls (39.13%). A significant difference (p < or = 0.01) in the overall proportions of waveform types was identified where the treatment group exhibited 41.30% abnormal waveforms, compared to 23.91% by controls. Additionally, two athletes (1 treatment, 1 control) demonstrated abnormal left ventricular wall motions (Type III) analogous to impaired left ventricular performance. The results indicated: (a) highly strength trained athletes with no history of anabolic-androgenic steroid usage exhibited an unexpected high incidence of Type II waveforms (28.26% pre/23.91% post); (b) a comparable group of strength trained athletes using anabolic-androgenic steroids exhibited a significantly higher percentage of abnormal waveforms as compared to controls (34.78% pre/37.21% post). Based on these results, high intensity strength training with and without anabolic-androgenic steroid supplementation induced alterations in the left ventricular wall motion.